Implementation of Green Energy Initiatives in India: Status, Challenges and Solutions - Semwal, Sunil; Prasad, R. S.; Juneja, Pradeep (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*335.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927315);" role="presentation">There is growing interest in creating the smart grid mainly reducing carbon footprint and outage. Countries with the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*348.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957108);" role="presentation">vast population like china and India are in the race <span dir="ltr" style="left: calc(var(–scale-factor)*287.93px); top: calc(var(–scale-factor)*348.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965678);" role="presentation">for implementation of the smart grid pilot project in selected <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*361.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91287);" role="presentation">areas. However, there are some serious technological and economic constraints on their implementation. This paper <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913269);" role="presentation">is an exclusive study on the status, challenges, and possible solution related <span dir="ltr" style="left: calc(var(–scale-factor)*382.39px); top: calc(var(–scale-factor)*374.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926401);" role="presentation">to the technological aspects from India <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892153);" role="presentation">perspective. <span dir="ltr" style="left: calc(var(–scale-factor)*125.97px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889243);" role="presentation">Since <span dir="ltr" style="left: calc(var(–scale-factor)*154.13px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*172.35px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890842);" role="presentation">smart <span dir="ltr" style="left: calc(var(–scale-factor)*200.75px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882987);" role="presentation">meter <span dir="ltr" style="left: calc(var(–scale-factor)*229.28px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03762);" role="presentation">is an integral <span dir="ltr" style="left: calc(var(–scale-factor)*293.88px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902846);" role="presentation">component <span dir="ltr" style="left: calc(var(–scale-factor)*344.49px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*358.27px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*376.50px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890842);" role="presentation">smart <span dir="ltr" style="left: calc(var(–scale-factor)*404.80px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953051);" role="presentation">micro <span dir="ltr" style="left: calc(var(–scale-factor)*434.04px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964219);" role="presentation">grid <span dir="ltr" style="left: calc(var(–scale-factor)*456.08px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927164);" role="presentation">implementation, <span dir="ltr" style="left: calc(var(–scale-factor)*527.29px); top: calc(var(–scale-factor)*388.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*401.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953914);" role="presentation">technological issue and challenges are particularly discussed in this paper. An actual implementation of a smart <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*414.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914322);" role="presentation">meter for Indian domestic consumers in laboratory environment shows the possibility of its adoption in residences.